Open eco-innovations in sustainable product development: Model framework of design thinking in quality life cycle assessment (DT-QLCA) - Dominika Siwiec; Bożena Gajdzik; Remigiusz Gawlik; Radosław Wolniak; Andrzej Pacana (Journal of Open Innovation: Technology, Market and Complexity)
Sustainable product development requires integrating eco- and open innovation. Traditional Design Thinking (DT), while effective for iterative product improvement, often lacks the capability to address environmental considerations comprehensively, necessitating new approaches to balance consumer needs with ecological stewardship. Despite growing attention to sustainability, existing methodologies fail to integrate consumer-focused innovation with systematic environmental responsibility. We tried to bridge this research gap by combining DT with Quality Life Cycle Assessment (QLCA) model to support eco-innovation within sustainable product design. This study aims to answer two research questions: 1) How can DT be integrated with QLCA to support open innovations in sustainable product development? 2) How can the DT-QLCA framework enhance decision-making processes in product design to align sustainability goals with customer expectations? Its objective is to develop a holistic framework that facilitates sustainable innovation while maintaining market competitiveness. An interdisciplinary DT-QLCA framework, integrating quality and sustainability metrics into the early stages of product development was developed. DT-QLCA bridges DT and environmental assessment, creating a structured decision-making tool that supports resource optimization, reduced environmental impact, and enhanced customer satisfaction. It can be applied in manufacturing industry for product designing and production management, bringing also added value for the environment and society.